2019
DOI: 10.4049/jimmunol.1900047
|View full text |Cite
|
Sign up to set email alerts
|

Complement Component C5 and TLR Molecule CD14 Mediate Heme-Induced Thromboinflammation in Human Blood

Abstract: Heme is a critical danger molecule liberated from hemeproteins in various conditions, including from hemoglobin in hemolytic diseases. Heme may cause thromboinflammatory damage by activating inflammatory and hemostatic pathways, such as complement, the TLRs, coagulation, and platelets. In this study, we explored the effect of single and dual inhibition of complement component C5 and TLR coreceptor CD14 on heme-induced thromboinflammation in an ex vivo human whole blood model. Heme induced a dose-dependent acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…Recently the heme-induced thrombogenecity was studied in an ex vivo human whole blood model. Heme-induced thromboinflammation was attenuated by the inhibition of the complement component C5 and the TLR coreceptor CD14 (141). Inhibition of the thromboinflammatory loop can be a meaningful therapeutic target in hemolytic diseases (141).…”
Section: Complement Activation and The Thromboinflammatory Loopmentioning
confidence: 99%
“…Recently the heme-induced thrombogenecity was studied in an ex vivo human whole blood model. Heme-induced thromboinflammation was attenuated by the inhibition of the complement component C5 and the TLR coreceptor CD14 (141). Inhibition of the thromboinflammatory loop can be a meaningful therapeutic target in hemolytic diseases (141).…”
Section: Complement Activation and The Thromboinflammatory Loopmentioning
confidence: 99%
“…Heme, but not Hb, is a potent modulator of the innate immune complement system [9] (Figure 4A). It inhibits the target molecules’ recognition by the classical complement pathway initiating protein C1q (Roumenina et al 2011), but activates the alternative complement pathway [121,129,130,131,132]. The first evidence for heme-mediated complement activation came in 1978, when Wilson et al showed in vitro that the addition of hemoglobin solutions (prepared from erythrocyte lysates from healthy or sickle cell patients) to human serum triggered activation of the alternative complement pathway, revealed by the presence of C3 and persistent FB cleavage products.…”
Section: Harmful Effects Of Heme On Endotheliummentioning
confidence: 99%
“…For instance, the ability of LPS to activate TLR4 depends on CD14, a glycophosphatidylinositol-anchored protein and co-receptor of MD-2 for LPS recognition ( 45 ), which may also control internalization of heme via TLR4 ( 10 ). Interestingly, soluble TLR4 co-receptor CD14 has recently been reported to mediate pro-inflammatory effects of heme in a whole blood model ( 46 ).…”
Section: Indirect Regulation Of Tlr4 Signaling By Hemementioning
confidence: 99%